2017
DOI: 10.4212/cjhp.v70i2.1648
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship Initiative in Treatment of Urinary Tract Infections at a Rehabilitation and Complex Continuing Care Hospital

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…This is why the use of ampicillin in empirical therapy of UTI as a single agent is neither appropriate nor recommended. Amoxicillin-clavulanic acid was recommended as an alternative empiric therapy for uncomplicated cystitis or a first-line therapy for moderate pyelonephritis [ 14 ]. In this study, more than one-third of the E. coli isolates were resistant to a combination of amoxicillin-clavulanic acid (34.3%), and higher resistance rates were observed in cases of K. pneumoniae (75.0%) and P. mirabilis (60.0%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why the use of ampicillin in empirical therapy of UTI as a single agent is neither appropriate nor recommended. Amoxicillin-clavulanic acid was recommended as an alternative empiric therapy for uncomplicated cystitis or a first-line therapy for moderate pyelonephritis [ 14 ]. In this study, more than one-third of the E. coli isolates were resistant to a combination of amoxicillin-clavulanic acid (34.3%), and higher resistance rates were observed in cases of K. pneumoniae (75.0%) and P. mirabilis (60.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Amoxicillin plus clavulanic acid (AMC) is recommended as first-line-therapy for mild and moderate pyelonephritis or complicated UTI and as alternative empiric therapy for uncomplicated cystitis. In the case of complicated UTI or severe pyelonephritis, amoxicillin with gentamicin or a second-generation cephalosporin with an aminoglycoside are recommended as first-line empiric therapy, and third-generation cephalosporin applied intravenously as alternative empiric therapy [ 13 , 14 ]. Uropathogens change, and their antibiotic resistance has increased over the past years, becoming an important problem worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are the commonest reported bacterial infections in long term care facilities and this leads to increased use of antibiotics of which 50% of cases are believed to signify asymptomatic bacteriuria [31]. The trend of routine screening of asymptomatic bacteriuria is injurious to the patient as it increases the rates of recurrent infections with drug resistant bacteria due to increased selective pressure [32, 33]. In the current study, the increased number of urine specimens from inpatients (Fig 1D) may be the result of routine screening of asymptomatic bacteriuria perhaps due to the increased number of student interns working in these inpatient departments at NTH but the trend could reduce if or when UTI routine screening targets symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms of E. coli resistance to quinolones and fluoroquinolones are related to the presence of efflux pumps and decreased uptake of the antibiotics due to changes in the outer membrane porin proteins (Asadi Karam et al 2019). Abdelhamid and Abozahra (2017) showed that the increased expression of the efflux pump-coding genes acrA and mdfA was related to the growing resistance to levofloxacin, which confirms that efflux pump systems contribute to fluoroquinolone resistance in urinary E. coli isolates.…”
Section: Mechanisms Of Upec Resistance To Antibioticsmentioning
confidence: 92%
“…UPEC producing ESBL are particularly often detected in developing countries (Iran -37.1%, Nepal -38.9%, Pakistan Kot B. 4 410 -40%, and Jordan -about 50%) (Ali et al 2016;Parajuli et al 2017;Shakhatreh et al 2018). Prasada et al (2019) revealed that in India the percentage of ESBL-producing UPEC increased from 45.2 to 59.6% over 5 years (2013)(2014)(2015)(2016)(2017). The frequency of ESBL-producing E. coli isolates is different in various parts of the world and sometimes even in various hospitals within the country.…”
Section: Mechanisms Of Upec Resistance To Antibioticsmentioning
confidence: 99%